Developing of Multiculturalism in the Pesantren: Study on KH Abdul Muhaimin and the Pesantren of Nurul Ummahaat - Hidayatullah, Syarif (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2016)
The article describes a case study on KH Abdul Muhaimin and his Pesantren of Nurul Ummahat who has a curious awareness and some real actions to growing up multiculturalism consciousness. The study results that Kyai recognizes a vision of the pesantren with three words: Modernity, Moderates, and Humanity, that viewed to respond any challenges and opportunities of the modernization and the globalization, including multiculturalism awareness. So, the Kyai elaborates about nationalism based on theological perspective, beside sociological and cultural. Theologically, the Kyai views that any human being must be recognized rightly at all, and do not depend on their position and entity. In this context, the Kyai and his Pesantren of Nurul Ummahat had done several actions, namely: academic discussions, dialogues among religious peoples, launching of FPUB, the Toya Mili movement, and the Palem Consortium. The article intends become a solution for the government, especially in creating new policies to respond radicalism in the pesantrens.